Detection of Babesia bigemina infection: use of a DNA probe - a review - Gerald M. Buening; Julio V. Figueroa (Memorias do Instituto Oswaldo Cruz, 1992)
The development of a repetitive DNA probe for Babesia bigemina was reviewed. The original plasmid (p(Bbi)16) contained an insert of B. bigemina DNA of approximately 6.3 kb. This probe has been evaluated for specificityand analytical sensitivity by dot hybridization with isolates from Mexico, the Caribbean region and Kenya. A partial restriction map has been constructed and insert fragments have been subcloned and utilized as specific DNA probes. A comparison of 32P labelled and non-radioactive DNA probes was presented. Non-radioctive detection systems that have been used include digoxigenin dUTP incorporation, and detection by colorimetric substrate methods. Derivatives from the original DNA probe have been utilized to detect B. bigemina infection in a) experimentally inoculated cattle, b) field exposed cattle, c) infected Boophilus microplus ticks, and d) the development of a PCR amplification system.